Trade and Inequality in Europe and the US - David Dorn; Peter Levell (Institute of Labor Economics (IZA), 2021)
The share of low-income countries in global exports nearly tripled between 1990 and 2015, driven largely by the rapid emergence of China as an exporting powerhouse. While research in economics had long acknowledged that trade with lower-income countries could raise income inequality in Europe and the US, empirical estimates indicated only a modest contribution of trade to growing national skill premia. However, if workers are not highly mobile across firms, industries and locations, then the unequal impacts of trade can manifest along different margins. Recent evidence from countries across Europe and the US shows that growing import competition from China differentially reduced earnings and employment rates for workers in more trade-exposed industries, and for the residents of more trade-exposed geographic regions. These adverse impacts were often largest for lower-skilled individuals. We show that domestic manufacturing employment declined much more in countries that saw a large growth of net imports from China (such as the UK and the US), than in countries that maintained relatively balanced trade with China (such as Germany and Switzerland). Drawing on a new analysis for the UK, we further show that trade with China contributed to job loss in manufacturing, but also to substantial declines in consumer prices. However, while the adverse labour market impacts were concentrated on specific groups of workers and regions, the consumer benefits from trade were widely dispersed in the population, and appear similarly large for high-income and low-income households. Globalisation has thus created pockets of losers, and recent evidence indicates that in addition to financial losses, residents of regions with greater exposure to import competition also suffer from higher crime rates, a deterioration of health outcomes, and a dissolution of traditional family structures. We argue that new import tariffs such as those imposed by the US in 2018 and 2019 are unlikely to help the losers from globalisation. Instead, displaced workers may be better supported by a combination of transfers to avert financial hardship, skills training that facilitate reintegration into the labour market, and place-based policies that stimulate job creation in depressed locations.
Keywords: E31; F13; F14; F16; F23; I14; I38; J21; J23; J31; J61; J62; R11; 330; trade; globalisation; inequality; employment; wages; consumer prices; public policy